Comportamento agronômico do milho em resposta ao modo de aplicação e concentrações de Azospirillum brasilense - Sá Júnior, Adílio de (2012)
The use of Azospirillum genus bacteria to fix nitrogen can be useful to obtain such chemical element and, thus, reduce costs of maize cultivation. This study aimed to evaluate changes of morphological components in the production and productivity of maize as a response to application methods and concentration of Azospirillum brasilense. The experiment was carried out at Gloria experimental farm, linked to Universidade Federal de Uberlândia, state of Minas Gerais. Randomized blocks with six replications were used as experimental design. Treatments were arranged in a factorial scheme (3 X 4 + 2). The first factor consisted of two ways of spray application, one in the furrow at the base of the plant, the other at the whole plant area. The second factor consisted of different doses of inoculating (100, 200, 300 and 400 mL ha 1). Additional treatments included seed treatment by Azospirillum brasilense inoculation at 100 mL ha 1 and not inoculated seeds. The development of crop and agricultural practices relating to the management of weeds, pests and diseases were performed by the use of high technology. Evaluation focused on morphological components (plant height, green leaves, cob diameter, dry straw, length, diameter) and production components (initial and final stands, number of rows and of grains per spike, spike length and thousand grain weight and yield). It was concluded that inoculation with Azospirillum brasilense via seed treatment increases maize yield and that inoculum application via spraying and the increasing in dosage do not alter the yield of maize.